(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Genital organ prolapse is a less-reported problem in Bangladesh. Surgery is needed only if the condition causes symptoms or interferes with her normal activities. Removal of the uterus and attaching the uterosacral ligaments to the posterior vaginal cuff and the cul-de-sac peritoneum in order to close off the sac and prevent subsequent prolapse is known as McCall culdoplasty. It was a prospective clinical trial. A total of 125 women were included purposively in this study who were admitted at Chattogram General Hospital, Bangladesh, for stage 2-4 uterovaginal prolapse and underwent Modified McCall culdoplasty during vaginal hysterectomy in the year 2018 and they were followed up-in the immediate post operative period, after 6 months, 12 months and 24 months. Six gynaecologists who were experienced in this operation assessed the eligibility of patients. Mean age of the study population was 55±3.6 and BMI (Kg/m 2 ) was 22 ± 1.8. While median of parity was 4(3-6). Majority (64%) underwent VH ± Bilateral salpingo-oophorectomy (BSO) and McCall culdoplasty and Pelvic floor repair (Anterior colporraphy and posterior colpoperineorrhaphy). Along with VH bilateral salpingo-oophorectomy (BSO) and McCall culdoplasty, anterior colporraphy was done in 12% cases and posterior colpoperineorrhaphy was done in another 12% cases. Blood transfusion was needed in 10 patients. 2 patients underwent laparotomy and Colpotomy was performed in 1 case due to complications. Stage 1 vault prolapse was identified in 4 cases at 12 months and 9 cases at 24months. Only 1 patient developed stage 2 vault prolapse. Vaginal length to the extent of >7cm was maintained in 88 cases. Intromission dyspareunia was experienced by 4 patients. No cases complained of profound dyspareunia. The McCall culdoplasty did not lead to a disruption of the vaginal axis and gave excellent anatomical and functional results in maintaining support after vaginal hysterectomy especially in sexually active patients. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 35-40